The complex relation between morality and empathy - Decety, Jean; Cowell, Jason M. (Trends in cognitive sciences, 2014)
Morality and empathy are fundamental components of human nature across cultures. However, the wealth of empirical findings from developmental, behavioral, and social neuroscience demonstrates a complex relation between morality and empathy. At times, empathy guides moral judgment, yet other times empathy can interfere with it. To better understand such relations, we propose abandoning the catchall term of empathy in favor of more precise concepts, such as emotional sharing, empathic concern, and affective perspective-taking.